1090. HHV-6 Encephalitis following Chimeric Antigen Receptor T-cell Therapy: Report of 2 Cases. (31st December 2020) - Rebechi, Melanie T; Bork, Jacqueline; Riedel, David J
Abstract: Background: Human herpesvirus 6 (HHV-6) is the most common cause of infectious encephalitis following hematopoietic stem cell transplant. Chimeric antigen receptor T-cell (CAR-T) therapy is a novel cancer-directed immunotherapy; chemotherapy conditioning for CAR-T results in prolonged, severe immunosuppression. HHV-6 encephalitis has not been reported in patients after CAR-T therapy. Methods: We report 2 cases of HHV-6 encephalitis after CAR-T therapy. Results: Case 1: A 69 year old man underwent CAR-T therapy after fludarabine/cyclophosphamide (Flu/Cy) conditioning for relapsed diffuse large B cell lymphoma (DLBCL). His course was complicated by cytokine release syndrome (CRS) requiring tocilizumab and neurotoxicity requiring high dose dexamethasone. On day 29 he was febrile to 39.3℃, confused, and had difficulty speaking. Mental status (MS) worsened, so LP and MRI of the brain were performed. HHV-6 CSF PCR was positive, and ganciclovir (GCV) was started. He improved gradually over 10 days. At follow up, he reported mild short term memory difficulty but no focal deficits. Case 2: A 57 year old man underwent CAR-T therapy after Flu/Cy conditioning for refractory DLBCL. His course was complicated by CRS requiring tocilizumab. On day 6, he had difficulty concentrating, slowed thinking, stuttering and repetitive speech. MS continued to worsen, and dexamethasone and siltuximab were given for CAR-T neurotoxicity. After 1 week he was following commands. By week 3 he remained intermittently confused and agitated, so MRI and LP were performed. HHV-6 PCR was positive in the CSF. He was started on GCV and improved gradually over the next 2 weeks but remained dysarthric with slowed speech. On day 55, HHV-6 remained detectable in CSF but not quantifiable and GCV was discontinued despite persistent cognitive deficits. Table 1: Demographics and clinical characteristics of 2 patients with HHV-6 encephalitis following CAR-T therapy Conclusion: Diagnosing HHV-6 encephalitis can be challenging after CAR-T therapy because altered MS is often attributed to CAR-T associated neurotoxicity. It is important to maintain a high index of suspicion for infectious causes of altered MS after CAR-T therapy, including HHV-6 encephalitis, especially in patients treated with further immunosuppression for CRS and CAR-T related neurotoxicity. Disclosures: All Authors : No reported disclosures